Prevalence and determinants of suboptimal health status among outdoor labor workers in Chengdu, Southwest China: A cross-sectional study - Lanchuan Zhang; Xue Li; Junwei Wang; Ping Shao; Qiaojing Gao (PLoS ONE, 2026)
Background Suboptimal health status, termed sub-health, is a global public health problem. It is an intermediate health condition between health and disease. This study aimed to investigate the prevalence of chronic sub-health conditions among outdoor labor workers in Chengdu (a major city in Southwest China) and identify its associated risk factors. Methods The Sub-Health Measurement Scale Version 1.0 (SHMS V1.0) was used to investigate the occurrence of sub-health conditions and their risk factors. Participants from four main outdoor occupations (drivers, construction workers, security guards, couriers) were surveyed to analyze the occurrence of sub-health and the associations between sub-health and other socio-demographic factors as well as exercise habits, using Pearson's correlation analysis and the multifactorial binary logistic regression model. Results A total of 1030 questionnaires were distributed and 902 questionnaires were recovered (88% recovery rate). Excluding the invalid questionnaires due to omitted questions, multiple choices, etc., 705 questionnaires were retained (78% validity rate) and the prevalence of varying degrees of sub-health was 80.28%. Several significant correlating factors of the sub-health condition were identified, such as age, year of outdoor service, marital status, family size, monthly income, drinking habit, and regular participation in exercise. Conclusions The incidence of subhealth was relatively high among outdoor workers, while no significant age-related difference was observed. The incidence also varies across the different occupations ( i.e. , drivers > security guards > construction workers > couriers). Future targeted measures to alleviate these contributing factors may improve the sub-health status of outdoor labor workers.